Nanoplasmonic‐Enhanced Spintronic Terahertz Emission (Adv. Mater. Interfaces 2/2022). Issue 2 (14th January 2022) - Liu, Shaojie; Guo, Fengwei; Li, Peiyan; Wei, Gaoshuai; Wang, Chun; Chen, Xinhou; Wang, Bo; Zhao, Weisheng; Miao, Jungang; Wang, Li; Xu, Yong; Wu, Xiaojun
Abstract : Nanoplasmonic‐Enhanced Spintronic Terahertz Emission In article number 2101296, Shaojie Liu, Yong Xu, Xiaojun Wu, and co‐workers demonstrate that nanoplasmonic resonance can effectively enhance the spintronic THz radiation from W/CoFeB/Pt heterostructures by 140%. The enhanced THz emission properties are systematically investigated through varying the pumping laser incidence direction, polarization, and the gold nanorods dimension parameters. Theoretical interpretations combined with Drude–Lorentz model and numerical simulations semi‐quantitatively reproduce the experimental results.